2018
DOI: 10.19159/tutad.449243
|View full text |Cite
|
Sign up to set email alerts
|

Determining Factors Affecting Cigarette Use of Students: The Case of Ondokuz Mayıs University, Samsun, Turkey

Abstract: Araştırmanın amacı, Ondokuz Mayıs Üniversitesi öğrencilerinin sigara kullanımını etkileyen faktörleri belirlemektir. Araştırma verileri, 384 öğrenciyle yapılan anketlerden oluşmaktadır. Sigara kullanan ve kullanmayan öğrenciler arasındaki farklılığın belirlenmesinde ki-kare testi, grup ortalamalarının karşılaştırılmasında t testi kullanılmıştır. Öğrencilerin sigara kullanımını etkileyen faktörler ise binary lojistik regresyon analiziyle belirlenmiştir. Araştırma sonuçları, erkek öğrencilerin kızlara oranla dah… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…Additionally, societal gender roles and attitudes towards smoking could have a significant impact on the acceptability of this behavior. Many clinical researches on smoking addiction compare usage rates in men and women, and similar to our study, discuss the high smoking rates among men [23,24]. The higher average age in the smoking group suggests that individuals may be more likely to start smoking or continue smoking as they age.…”
Section: Discussionsupporting
confidence: 82%
“…Additionally, societal gender roles and attitudes towards smoking could have a significant impact on the acceptability of this behavior. Many clinical researches on smoking addiction compare usage rates in men and women, and similar to our study, discuss the high smoking rates among men [23,24]. The higher average age in the smoking group suggests that individuals may be more likely to start smoking or continue smoking as they age.…”
Section: Discussionsupporting
confidence: 82%
“…Yılmaz et al they showed that male students studying in sports sciences were more likely to consume cigarettes and alcohol, but there was no statistical difference (Yılmaz et al, 2007). In another study conducted with university students, it was determined that male students consumed more cigarettes (p<0.05) due to a greater sense of freedom and less family pressure (Kılıç et al, 2018). When the physical activity levels were examined in our study, it was observed that the students who were inactive or did insufficient physical activity were more in health sciences, those who had sufficient level in sports sciences (p<0.05).…”
Section: Discussionmentioning
confidence: 53%